Situation Report: Romania, 2 April 1981 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Foreign Minister Stefan Andrei Visits ASEAN Countries Romanian-West German Relations New Espionage Scandal Romanian-Soviet Trade in 1980 Ceausescu's Speech at CC Plenum Document on the Party's Strength and Composition Ceausescu's Speech to the Agricultural Congress Youth and Industrialization